The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/inf.0000000000003400
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Cytomegalovirus Infection of Preterm and Very-low-birth-weight Infants Through Maternal Breast Milk: Does It Matter?

Abstract: Background: Postnatal infection with cytomegalovirus (CMV) in verypreterm and very-low-birth-weight infants, transmitted through breast milk (BM), is potentially associated with adverse outcomes. This study aimed to investigate the incidence and clinical significance of postnatal CMV infection in a tertiary neonatal intensive care unit. Methods: Infants of CMV-seropositive mothers born in a neonatal intensive care unit in Melbourne, Australia, were observed for 14 weeks from birth in a prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…One study did not report the birth weight of the infants studied [ 14 ]. Five studies reported outcomes for BPD diagnosed at postnatal age 28 days [ 13 , 14 , 17 , 28 , 31 ], and thirteen studies reported outcomes for BPD diagnosed at 36 weeks of postmenstrual age [ 12 , 14 16 , 18 , 20 , 28 34 ]. One study extracted data from a database using diagnostic codes only and did not account for diagnostic criteria for BPD [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study did not report the birth weight of the infants studied [ 14 ]. Five studies reported outcomes for BPD diagnosed at postnatal age 28 days [ 13 , 14 , 17 , 28 , 31 ], and thirteen studies reported outcomes for BPD diagnosed at 36 weeks of postmenstrual age [ 12 , 14 16 , 18 , 20 , 28 34 ]. One study extracted data from a database using diagnostic codes only and did not account for diagnostic criteria for BPD [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a study involving very low birth weight neonates in intensive care units found that postnatal CMV infection through breast milk significantly increased the risk of mortality and bronchopulmonary dysplasia [17]. However, long-term consequences of CMV infection transmitted through contaminated breast milk have not been reported [24]. A recent study by Midgley et al (2020) has reported that, compared to formula feeding and caesarean section, breastfeeding and vaginal delivery respectively increase the likelihood of postnatal CMV infection (OR=3.801, 95% CI: 2.474-5.840, p<0.001; OR=1.818, 95% CI: 1.190-2.196, p<0.001) [25].…”
Section: Childbirth and Breastfeedingmentioning
confidence: 99%
“…Risk factors for infant symptomatic infection include VLBW, gestational age < 32 weeks, and level of DNA lactia [77••]. Three systematic reviews [78][79][80] published regarding CMV transmission via untreated or fresh breast milk found a rate of transmission to infants between 19 and 25%.…”
Section: Postnatal Cytomegalovirus Infection Prevalence and Presentat...mentioning
confidence: 99%